Dependence of Echovirus 9 on the Enterovirus RNA Replication Inhibitor 2-(α-Hydroxybenzyl)-Benzimidazole Maps to Nonstructural Protein 2C - Hadaschik, Dirk (American Society for Microbiology, 1999)
HBB [2-(α-hydroxybenzyl)-benzimidazole] selectively inhibits RNA synthesis of most enteroviruses. However, isolation of HBB-dependent variants is possible. Sequence analysis and characterization of recombinant viruses revealed that HBB dependence maps to the nonstructural protein 2C. A single point mutation at position C(4782)U is sufficient to establish the HBB-dependent phenotype in our echovirus 9 model.